A case report of hereditary spherocytosis (HS): Approach to diagnosis and management of HS - Chandra Babu, Aruna; Francis, Johny Vakayil; George, Ditty; Kuriakose, Mathews E (Indian Journal of Case Reports, 2022)
Hereditary spherocytosis (HS) is a type of congenital hemolytic anemia, in which heterogeneous alterations in one of the six genes that encode for proteins involved in vertical associations which tie the red blood cell (RBC) membrane skeleton to the lipid bilayer causesdysfunction or deficiency of cell membrane protein resulting in spherical-shaped, hyper- dense, and poorly deformable RBCs with a shortened life span. We report a case of HS in a 2-month-old female who presented with severe anemia, jaundice, and hepatosplenomegaly.The peripheral blood smear showed spherocytosis and reticulocytosis. The osmotic fragility was positive and direct antiglobin test was negative. The osmotic fragility test and direct antiglobulin test were positive. She was managed with packed RBCs (PRBCs) transfusionand folic acid supplementation.